PENGARUH BUDAYA ORGANISASI DAN PEMBERIAN MOTIVASI TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA BPJS KETENAGAKERJAAN CABANG PANAM PEKANBARU - Mansiz, Ilham; Kasmiruddin, Kasmiruddin (Komunitas Manajemen Kompetitif, 2024)
Abstract: This study aims to analyze the influence of organizational culture and motivation on employee organizational commitment at BPJS Employment Panam Pekanbaru Branch. This study uses organizational culture and motivation as independent variables, and employee organizational commitment as dependent variables. This study uses a quantitative method. The research sample was 53 respondents, with data collection techniques using questionnaires. The data obtained was analyzed using SPSS. The results of the study show that the organizational culture and motivation at BPJS Ketenagakerjaan Cabang Panam Pekanbaru are categorized as strong/good, and the organizational commitment of employees is categorized as quite good. The results of hypothesis testing show that organizational culture has an influence on employee organizational commitment. Providing motivation has an influence on the commitment of the employee organization. Simultaneously, organizational culture and motivation affect the organizational commitment of employees at BPJS Ketenagakerjaan Cabang Panam Pekanbaru. Keywords: Organizational Culture, Motivation, Employee Organizational Commitment